Emerging Antioxidant Paradigm of Mesenchymal Stem Cell-Derived Exosome Therapy - Xia, Chen; Dai, Zhanqiu; Jin, Yongming; Chen, Pengfei (Frontiers in Endocrinology, 2021)
Mesenchymal stem cell-derived exosomes have been under investigation as potential treatments for a diverse range of diseases, and many animal and clinical trials have achieved encouraging results. However, it is well known that the biological activity of the exosomes is key to their therapeutic properties; however, till date, it has not been completely understood. Previous studies have provided different explanations of therapeutic mechanisms of the exosomes, including anti-inflammatory, immunomodulatory, and anti-aging mechanisms. The pathological effects of oxidative stress often include organ damage, inflammation, and disorders of material and energy metabolism. The evidence gathered from research involving animal models indicates that exosomes have antioxidant properties, which can also explain their anti-inflammatory and cytoprotective effects. In this study, we have summarized the antioxidant effects of exosomes in in vivo and in vitro models, and have evaluated the anti-oxidant mechanisms of exosomes by demonstrating a direct reduction in excessive reactive oxygen species (ROS), promotion of intracellular defence of anti-oxidative stress, immunomodulation by inhibiting excess ROS, and alteration of mitochondrial performance. Exosomes exert their cytoprotective and anti-inflammatory properties by regulating the redox environment and oxidative stress, which explains the therapeutic effects of exosomes in a variety of diseases, mechanisms that can be well preserved among different species.